(untitled) (Global Journal of Medical Research, 2020)
In the current pandemic context linked to COVID 19, which has and which continues to mark our daily lives, we considered useful to share our data concerning pregnant women affected by this disease at the level of the province of Meknes (Morocco), which is a province of 835,695 inhabitants. Our experience concerns 11 patients confirmed positive for COVID, collected since the start of the pandemic in our country on 02/03/2020 to date on 01/10/2020 based on the data recorded in patient files archived at the level of the provincial reference center. This work traces the symptoms, diagnosis, treatment, management methods, and the evolution of the various parturients to date. The conclusion of this work remains comparable to the literature with one particularity: the care and the follow-up of 10 patients out of 11 (91%) was done with medical surveillance at home.